Ab Initio Crystal Field for Lanthanides. Issue 15 (20th February 2017) - Ungur, Liviu; Chibotaru, Liviu F.
Abstract: An ab initio methodology for the first‐principle derivation of crystal‐field (CF) parameters for lanthanides is described. The methodology is applied to the analysis of CF parameters in [Tb(Pc)2 ] − (Pc=phthalocyanine) and Dy4 K2 ([Dy 4 K 2 O(O t Bu) 12 ]) complexes, and compared with often used approximate and model descriptions. It is found that the application of geometry symmetrization, and the use of electrostatic point‐charge and phenomenological CF models, lead to unacceptably large deviations from predictions based on ab initio calculations for experimental geometry. It is shown how the predictions of standard CASSCF (Complete Active Space Self‐Consistent Field) calculations (with 4 f orbitals in the active space) can be systematically improved by including effects of dynamical electronic correlation (CASPT2 step) and by admixing electronic configurations of the 5 d shell. This is exemplified for the well‐studied Er‐trensal complex (H3 trensal=2, 2′, 2"‐tris(salicylideneimido)trimethylamine). The electrostatic contributions to CF parameters in this complex, calculated with true charge distributions in the ligands, yield less than half of the total CF splitting, thus pointing to the dominant role of covalent effects. This analysis allows the conclusion that ab initio crystal field is an essential tool for the decent description of lanthanides. Abstract : A fully ab initio methodology for the unique determination of the parameters of the crystal field in lanthanide complexes is presented and contrasted with experimental, phenomenological, and electrostatic models. It is found that the metal–ligand covalence gives the dominant contribution to the crystal field in lanthanides.